Empirical studies on the impacts of ICT usage in Europe - Martin Falk; Federico Biagi (European Commission, Joint Research Centre (JRC), 2015)
This report has three sections and a key feature of our empirical analysis is the use of several types of advanced ICT activities such as enterprise resource planning systems, mobile internet access and e-commerce practices. The first section presents new empirical evidence regarding the impact of ICT/E-commerce activities on industry performance in Europe measured as employment and labour productivity growth. The data consists of multi-country industry level data for 14 European countries for the period 2002-2010. The main result of this section is that the increase in ICT/e-commerce activities over time has not lead to a decline in jobs. This holds true for both manufacturing and service industries. In contrast, the different types of ICT activities are significantly related to labour productivity. However, the sign and significance of the relationships vary across different types of ICT activities and also vary over time with lower magnitude for the more recent period. The second section looks at the relationship between several indicators of ICT usage and digitalisation, and the relative demand for highly skilled workers. The data is based on two-digit industry data for seven European countries for the period 2002-2010. For manufacturing industries, our estimates show that broadband connected employees, diffusion of mobile internet, use of enterprise resource planning systems and electronic invoicing are all significantly positively related to the industries' skill intensity. For service industries only mobile internet usage is significant. These estimates indicate that the increase in ERP systems during the period studied accounts for 25% of the increase in the share of workers with a tertiary degree across manufacturing industries and countries. The results are robust with respect to the estimation method and when accounting for endogeneity of ICT. The third section investigates the relationship between technological and organisational innovations, and ICT usage/e-commerce and internet technologies. The data is based on disaggregated data by firm size/industry for 12 European countries for the period 2002-2010. The empirical results show that the sales share of new market products is significantly positively related with both the percentage of workers with mobile internet access and e-procurement activities. Sharing electronic data also contributes to product innovations. We also find that organisational change and enterprise resource planning
Keywords: J23; J24; O33; L86; 330; Labour Demand; Technological Change; ICT; employment